ANALYSIS OF BLENDED LEARNING TEACHING METHODS ISLAMIC EDUCATION IN DIGITAL ERA - Farrel Feriansyah (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2023)
Abstract: In the contemporary digital era, education is undergoing a transformative shift, and Islamic education is no exception. This study delves into the analysis of blended learning teaching methods within the context of Islamic education, exploring the intersection of traditional pedagogical approaches and digital technologies. The research employs a mixed-methods approach, combining qualitative and quantitative data collection methods to provide a comprehensive understanding of the effectiveness and challenges associated with blended learning in Islamic education. A review of the existing literature establishes the theoretical framework, emphasizing the need for adaptive teaching methods that align with the demands of the digital age while preserving the core values of Islamic education.The qualitative component involves interviews and focus group discussions with educators, students, and educational administrators, aiming to capture the perspectives, experiences, and attitudes towards blended learning in Islamic education. The study contributes to the growing body of literature on technology-enhanced education in the context of Islamic studies, providing insights that can inform pedagogical practices, curriculum design, and policy development. As the digital landscape continues to evolve, understanding the nuances of blended learning in Islamic education becomes imperative for educators, policymakers, and stakeholders seeking to ensure the holistic development of students in the modern era.